Profil dan Opini Pengguna Aplikasi Wisata “Jogja Istimewa” - Annisa Retnaningtyas (Gadjah Mada Journal of Tourism Studies, 2020)
Currently, smartphone applications unquestionably aid human activities. Smartphone applications in the tourism industry can help to grow the industry. In this case, user feedback is crucial in the development of travel applications. This study discusses the user profiles and opinions of the “Jogja Istimewa” mobile application, with a focus on the app’s usability. This study employed a quantitative approach in the form of an online questionnaire. User profiles are classified into six categories: age, gender, hometown, education, occupation, and internet quota. Meanwhile, the usability theory employed in this study is divided into three components: effectiveness, efficiency, and satisfaction, all of which are measured using a Likert Scale. This study compares user opinions based on each profile category. The questionnaire distribution resulted in 50 users of the mobile application “Jogja Istimewa.” The findings revealed that respondents have a wide range of profiles in terms of age, gender, origin, education, profession, and internet usage. The majority of usability statements received high scores (on a scale of 3,41-4,20), while some other statements received medium scores (scale 2,61-3,40).